Seroprevalence of SARS-CoV-2-specific anti-spike IgM, IgG, and anti-nucleocapsid IgG antibodies during the second wave of the pandemic: A population-based cross-sectional survey across Kashmir, India - Lone, Kouser Sideeq; Khan, S. Muhammad Salim; Qurieshi, Mariya Amin; Majid, Sabhiya; Pandit, Mohammad Iqbal; Haq, Inaamul; Ahmad, Javid; Bhat, Ashfaq Ahmad; Bashir, Khalid; Bilquees, Sufoora; Fazili, Anjum Bashir; Hassan, Muzamil; et al. (Frontiers in Public Health, 2022)
Background: We aimed to conduct this population-based study in the age group 7 years and above to estimate the seropositivity and its attributes in Kashmir valley. Methods: We conducted a community-based household-level cross-sectional study with a multistage, population-stratified, probability-proportionate-to-size, cluster sampling method to select 400 participants from each of the ten districts of Kashmir. We also selected a quota of health care workers, police personnel, and antenatal women from each of the districts. All family members with age seven years or more were invited to participate. Information was collected through a standardized questionnaire and entered into Epicollect 5 software. Trained health care personnel were assigned to collect venous blood samples from each of the participants, which were transferred and processed for immunological testing. Testing was done for the presence of SARS-CoV-2 specific anti-spike IgM, IgG antibodies, and anti-nucleocapsid IgG antibodies. Weighted seropositivity was estimated along with the adjustment done for the sensitivity and specificity of the test used. Findings: The data was collected from a total of 4229 participants from the general population within the ten districts of Kashmir. Our results showed that 84·84% (95% CI 84·51%-85·18%) of the participants were seropositive among the general population. Age group 45-59 years (odds ratio of 0·73; 95% CI 0·67-0·78), self-reported history of comorbidity (odds ratio of 1·47; 95% CI 1·33-1·61), and positive vaccination history (odds ratio of 0·85; 95% CI 0·79-0·90) were significantly related to seropositivity. The estimated infection fatality ratio was 0·033 % (95% CI: 0·034%-0·032%) between 22 May to 31 July 2021 against the seropositivity for IgM antibodies. Interpretation: During the second wave of the SARS-CoV-2 pandemic, 84·84% (95% CI 84·51%-85·18%) of participants from this population-based cross-sectional sample were seropositive against SARS-CoV-2. Despite a comparatively lower number of cases reported and lower vaccination coverage in the region, our study found such high seropositivity across all age groups, which indicates the higher number of the subclinical and less severe unnoticed caseloads in the community. Funding: The National Health Mission Jammu and Kashmir funded the study.